Role of age and birth month in infants hospitalized with RSV‐confirmed disease in the Valencia Region, Spain. Issue 2 (24th November 2021) - Mira‐Iglesias, Ainara; Demont, Clarisse; López‐Labrador, F. Xavier; Mengual‐Chuliá, Beatriz; García‐Rubio, Javier; Carballido‐Fernández, Mario; Tortajada‐Girbés, Miguel; Mollar‐Maseres, Juan; Schwarz‐Chavarri, Germán; Puig‐Barberà, Joan; Díez‐Domingo, Javier
Abstract: Background: RSV is the leading cause of hospital admissions in infants and the principal cause of bronchiolitis in young children. There is a lack of granular data on RSV‐associated hospitalization per season using laboratory confirmed results. Our current study addresses this issue and intends to fill this gap. Methods: The study was conducted from 2014 through 2018, in 4 to 10 hospitals in the Valencia Region, Spain. Infants included in this study were admitted in hospital through the Emergency Department with a respiratory complaint and tested by RT‐PCR for RSV in a central laboratory. Results: Incidence rates of RSV‐associated hospitalization varied by season and hospital. Overall, the highest incidence rates were observed in 2017/2018. RSV‐associated hospitalization was highest in infants below 3 months of age and in those born before or at the beginning of the RSV season. Almost 54% of total infants hospitalized with laboratory confirmed RSV were found to be born outside the season, from April to October. The RSV positivity rate by ICD‐10 discharged codes varied by season and age with results from 48% to 57% among LRI (J09‐J22). Conclusion: The study was instrumental in bringing forth the time unpredictability of RSV epidemics, the critical impact of age, and the comparable distribution of RSV‐associated hospitalization in infants born on either side of the RSV season. These data could help in better characterization of the population that drives the healthcare burden and is crucial for the development of future immunization strategies, especially with upcoming vaccines in against RSV.